Stellar feedback impact on the ionized gas kinematics in the dwarf galaxy Sextans A - Gerasimov, Ivan S.; Egorov, Oleg; Lozinskaya, Tatiana A; Moiseev, Alexei V; Oparin, Dmitry V (Monthly notices of the Royal Astronomical Society, 2022)
Feedback from massive stars shapes the interstellar medium (ISM) and affects the evolution of galaxies, but its mechanisms acting at the small scales (∼10 pc) are still not well constrained observationally, especially in the low-metallicity environments. We present the analysis of the ionized gas (focusing on its kinematics, which were never studied before) and its connection to the massive stars in the nearby (D ∼ 1.4 Mpc) star-forming very metal poor ($Z\sim 0.07 \, Z_\odot$) galaxy Sextans A. The analysis is based on the observations with a scanning Fabry-Perot interferometer, long-slit spectroscopy, and imaging in emission lines with narrow-band tunable filters. We found 10 expanding superbubbles of ionized gas with ages of 1-3 Myr. We argue that three of them are probable supernova remnants, while the pre-supernova feedback is an important source of energy for blowing out the remaining superbubbles. The two brightest sites of star formation exhibit signs of outflowing ionized gas, which is traced by its ionized and atomic gas kinematics and (in one case) by its emission line flux ratios. Overall, the ionized gas kinematics in Sextans A is highly affected by the feedback from several generations of massive stars and inconsistent with the mere solid-body rotation observed in atomic hydrogen.